Módulo de Manutenção Preditiva para o Sistrade ERP - Silva, José Pedro Moreira e (2021)
In recent years, manufacturing industries have faced a major change in manufacturing processes, especially in the pursuit of highly customized products, the shorter product life cycle, as opposed to traditional mass production of standard products. As a result of this change, organizations, as well as all sectors of manufacturing activity, face the need for adaptation. Maintenance is a major manufacturing process as it affects performance and production quality, having a direct impact on customer satisfaction and product cost. These days, corrective and planned maintenance strategies are widely implemented. However, manufacturing companies that can update and embrace the new reality by implementing new, innovative, and intelligent maintenance systems that can predict potential failures. Predictive maintenance tools and systems have been developed and continue to be studied and improved. However, industries have little confidence in these systems to implement in their facilities.